Pemberian Kacang-Kacangan terhadap Perubahan Asam Urat pada Mahasiswi di Asrama Mahasiswa Universitas Muhammadiyah - Sukesih, S; Hidayah, Noor; Ibrizah, Falikhatul (Prosiding University Research Colloquium, 2020)
Nuts are a food source of protein with high nutritional value (20-25 g / 100 g), vitamin B (thiamin, riboflavin, niacin, folic acid), minerals (Ca, Fe, P, K, Zn, Mg, etc.), and fiber but contain moderate and high purines, causing uric acid levels in the blood to rise. The purpose of this study: to determine the effect of the provision of nuts on gout changes in students in the Kudus University student dormitory. Research methods: the type of research used is a quasi experiment with the pretest posttest control group design data analysis using t test, the instrument of giving nuts using SOP. The population in the study was 196 female students sample 32 students with purposive sampling technique consisting of 16 female students of the intervention group and 16 female students of the control group. The results of the study with paired t test in the intervention group showed that the average level of uric acid prior to treatment was 3.08 mg / dl. after treatment 3.83 mg / dl. The mean difference between the before and after measurements is 0.77. The statistical test results obtained 0,000, it can be concluded that there is a significant difference between uric acid levels before and after treatment in the intervention group, while the independent t-test results obtained the average levels of uric acid in the intervention group who received the treatment of nuts are 3.83 mg / dl, while for the control group is 3.26 mg / dl. Statistical test results obtained p value = 0.016 means that there are significant differences in the average levels of uric acid in the intervention and control groups after treatment.